« Mon compte-rendu n’est que la défense continuée » : étude et analyse des écrits du for privé d’avocats de part et d’autre de la Révolution française à travers l’exemple des Mémoires de Dupin aîné - Aurore Sat (Criminocorpus)
For a long time, studies on lawyers, as for all the socio-professional groups, have been considering mostly the institutional sources, and rarely focused on personal, or even intimate, writings. Those texts, known as “ego-documents” today, are analysed in order to enlighten the history of barristers at a major time of their constitution and structuration in the French “barreau”, before and after the French Revolution. Reading these texts, we can find in them a reflect of their author’s identity, a mean of defending his profession and expressing his political opinions – that are for all of them conservative. The French lawyer Dupin, deputy and general attorney at the Cour de cassation is a very representative example with his Memoirs, published in 1852. Speaking of the second part of the era studied, they gather all the conclusions that can be made for a larger group and illustrate in the same time the different evolutions that can be noticed.